Construction of unique conductive networks in carbon nanotubes/polymer composites via poly(ε-caprolactone) inducing partial aggregation of carbon nanotubes for microwave shielding enhancement. (January 2023) - Tao, Jun-Ru; Luo, Cheng-Long; Huang, Ming-Lu; Weng, Yun-Xuan; Wang, Ming
Highlights: Unique conductive networks of individual CNTs and CNT clusters are constructed. Poly(ε-caprolactone) inducing partial aggregation of CNTs creates CNT clusters. The unique conductive networks show high conductivity and microwave SE. Balance amounts for CNTs and PCL exist for the unique conductive networks. Polymer pairs are important to form the unique conductive networks. Abstract: Herein, a unique conductive network, which includes individual carbon nanotubes (CNT) and some CNT clusters (CNT/CNT-cluster) formed via poly(ε-caprolactone) (PCL) inducing partial aggregation of CNTs, is constructed in CNTs filled CPCs. Three different kinds of polymers, which are isotactic polypropylene (PP), polystyrene (PS) and polylactic acid (PLA), are used to evaluate the effect of polymer matrix on the unique conductive network. A comparative study on the electrical conductivity and microwave shielding properties are also carried in these composites. The effect of CNTs and PCL loadings on the formation of CNT-clusters in the samples is also discussed in this study. Due to PCL inducing partial aggregation of CNTs and the good distribution of residue CNTs in PLA, the excellent CNT/CNT-cluster conductive network is formed in the CNT/PCL/PLA composites. Comparing with the traditional conductive network, the CNT/CNT-cluster conductive network exhibits high efficiency for improving electrical conductivity and microwave shielding property.